Pelaksanaan Pengadaan Pasokan Bahan Baku Karkas Ayam: Studi Kasus pada Rumah Makan “Ayam Bakar Wong Solo” Jember - Zahro, Fatimatuz; Poernomo, Djoko; Iswono, Sugeng (e-Sospol, 2016)
Abstract This research aimed to determine and describe the implementation of supply procurement of chicken carcass as the raw materials at “Ayam Bakar Wong Solo” Restaurant Jember that causes delays and unfulfillment of the quantity of chicken carcass ordered. The research used qualitative paradigm with case study design. Data were collected by in-depth interview, passive observation, and documentation. Data analysis used analyses of domain, taxonomy, and fishbone diagram. The result showed that "Ayam Bakar Wong Solo" Restaurant Jember worked with two suppliers of chicken carcass. The suppliers selection was based on price and quality of chicken carcass offered. However, the main consideration in prioritizing the supplier was the supplier’s ability to meet the demand of chicken carcass quantity. The factors that caused delay and unfulfillment of chicken carcass ordered were the environment and human.